Fractal patterns in riverbed morphology produce fractal scaling of water storage times. Issue 13 (14th July 2015) - Aubeneau, A. F.; Martin, R. L.; Bolster, D.; Schumer, R.; Jerolmack, D.; Packman, A.
Abstract River topography is famously fractal, and the fractality of the sediment bed surface can produce scaling in solute residence time distributions. Empirical evidence showing the relationship between fractal bed topography and scaling of hyporheic travel times is still lacking. We performed experiments to make high‐resolution observations of streambed topography and solute transport over naturally formed sand bedforms in a large laboratory flume. We analyzed the results using both numerical and theoretical models. We found that fractal properties of the bed topography do indeed affect solute residence time distributions. Overall, our experimental, numerical, and theoretical results provide evidence for a coupling between the sand‐bed topography and the anomalous transport scaling in rivers. Larger bedforms induced greater hyporheic exchange and faster pore water turnover relative to smaller bedforms, suggesting that the structure of legacy morphology may be more important to solute and contaminant transport in streams and rivers than previously recognized.